Sentiment Analysis of Related Public Opinion Smart City Pasuruan Regency on Media Social Using Svm Algorithm - Sony Nuhmana (Journal of Social Research, 2023)
Development in Pasuruan Regency is developed in a sustainable process, thus impacting daily community service activities. With interaction, the community feels what is done in the service process. With Smart City, these services are transformed into a more modern and computer-based form. Along with the development of social media. People often provide comments or opinions through social media, including Facebook.  Facebook is a social networking and microblogging service that makes it easier for users to read and send text-based messages. People's opinions are important information about their responses to district government programs, so they are important to record and analyze. The research conducted is an analysis of public opinion using the Support Vector Machine method. The most efficient method for text classification is the Support Vector Machine (SVM). SVM classification accuracy is 92.6%